Implementation of the Pancasila Student Profile Strengthening Project thru Video Media and Waste Sorting Practices for Early Childhood - Clarita Pratnya Anggana; Mustakimah Mustakimah; Sofa Muthohar (Universitas Ahmad Dahlan, 2025)
Instilling an environmentally conscious character from an early age is an important step in shaping a generation that is responsible toward nature. However, the implementation of learning that integrates digital media and hands-on practice in early childhood education still needs further study. This research aims to enhance children's understanding and skills in distinguishing between organic and inorganic waste thru educational video media and direct practice. At the same time, it aims to develop teachers' competencies in implementing the Pancasila Student Profile Strengthening Project at TK Hidayatul Mubtadiin. The method used is descriptive with a simple mixed-method approach thru field studies. Data were collected thru observation, interviews, and documentation of project activities. The project was carried out by presenting educational videos about the impact of littering, solutions for protecting the environment, and how to dispose of organic and inorganic waste. The subjects of the study were 22 kindergarten B children who participated in waste sorting practices based on the color of the trash bins. The research results show that 19 out of 22 children (86.4%) successfully separated organic and inorganic waste correctly, while 3 children (13.6%) experienced difficulties. This research indicates that learning thru educational videos and hands-on practice can enhance children's understanding and ability in waste sorting, as well as support the development of an environmentally conscious character in early childhood.